Does parental exposure to nanoplastics modulate the response of Hediste diversicolor to other contaminants: a case study with arsenic - Silva, M.S.S. (2022)
Plastic pollution is a serious problem in aquatic systems throughout the world. Despite the increasing number of studies addressing the impact of macro- and microplastics on biota, there is still a significant knowledge gap regarding the effects of nanoplastics alone and in combination with other contaminants. Among the aquatic contaminants that may interact with nanoplastics is arsenic (As), a metalloid found in estuarine and coastal ecosystems, pernicious to benthic organisms. This study aimed to understand how a parental pre-exposure to 100 nm polystyrene nanoplastics (PS NPs) would influence the response of Hediste diversicolor to exposure to arsenic in terms of behaviour, neurotransmission, antioxidant defences and oxidative damage, and energy metabolism. The obtained data revealed an increase in burrowing time and a significant inhibition in cholinesterase activity in all polychaetes exposed to As, regardless of the pre-exposure to PS NPs. Oxidative status was altered particularly in parentally exposed organisms, with damage detected in terms of lipid peroxidation at 50 μg/L and protein carbonylation at 50 and 250 μg As/L exposed organisms when compared to control. Overall, data shows that parental pre-exposure to plastics influences the response of aquatic organisms, increasing their susceptibility to other contaminants. Thus, more studies should be performed with other environmental contaminants, to better understand the potential increased risk associated with the presence of nanoplastics to aquatic ecosystems.